Simple modification of arm position improves B1+ and signal homogeneity in the thoracolumbar spine at 3T. Issue 1 (26th May 2017) - Ishizaka, Kinya; Kudo, Kohsuke; Harada, Kuniaki; Shirai, Toru; Fujiwara, Taro; Aoike, Suzuko; Takamori, Sayaka; Shirato, Hiroki
Abstract : Purpose: To evaluate the homogeneity of the radiofrequency magnetic field (B1 + ) and signal intensity using different arm positions during 3T thoracolumbar spinal imaging. Materials and Methods: Twenty volunteers were scanned with a four‐channel radiofrequency (RF) transmit coil at 3T, with arms on the bed (conventional), arms elevated by 100 mm (arm lift), or with the arms‐up position (elevated arm). Axial B1 + maps and sagittal T1 ‐weighted image (T1 WI)‐performed RF shimming were obtained for each arm position. The mean and standard deviation (SD) of the flip angle (FA) at the center of the vertebra on each B1 + map, and contrast noise ratios (CNRs) between the spinal cord and cerebrospinal fluid of sagittal T1 WI, were calculated and compared among the different arm positions. Results: Mean FA values (degrees) for the arm lift and elevated arm positions were significantly larger than for the conventional position ( P < 0.001 for both) at the twelfth thoracic vertebra (Th12). FA SD values for the arm lift and elevated arm position were significantly smaller than for the conventional position ( P < 0.001 for both) at Th12. CNR for the arm lift and elevated arm position were significantly higher than for the conventional position ( P = 0.007 and 0.002, respectively). The mean and SD of the FA and the CNR did not differ significantly for the arm lift and elevated arm positions ( P = 0.591, 0.958, and 0.927, respectively). Conclusion: Inhomogeneities of B1 + and signal intensities were improved by simply changing the arm position in 3T thoracolumbar spinal imaging. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:123–130.